Low genetic diversity in wide-spread Eurasian liver fluke Opisthorchis felineus suggests special demographic history of this trematode species. - Ilja I Brusentsov; Alexey V Katokhin; Irina V Brusentsova; Sergei V Shekhovtsov; Sergei N Borovikov; Grigoriy G Goncharenko; Lyudmila A Lider; Boris V Romashov; Olga T Rusinek; Samat K Shibitov; Marat M Suleymanov; Andrey V Yevtushenko; et al. (PLoS ONE)
Opisthorchis felineus or Siberian liver fluke is a trematode parasite (Opisthorchiidae) that infects the hepato-biliary system of humans and other mammals. Despite its public health significance, this wide-spread Eurasian species is one of the most poorly studied human liver flukes and nothing is known about its population genetic structure and demographic history. In this paper, we attempt to fill this gap for the first time and to explore the genetic diversity in O. felineus populations from Eastern Europe (Ukraine, European part of Russia), Northern Asia (Siberia) and Central Asia (Northern Kazakhstan). Analysis of marker DNA fragments from O. felineus mitochondrial cytochrome c oxidase subunit 1 and 3 (cox1, cox3) and nuclear rDNA internal transcribed spacer 1 (ITS1) sequences revealed that genetic diversity is very low across the large geographic range of this species. Microevolutionary processes in populations of trematodes may well be influenced by their peculiar biology. Nevertheless, we suggest that lack of population genetics structure observed in O. felineus can be primarily explained by the Pleistocene glacial events and subsequent sudden population growth from a very limited group of founders. Rapid range expansion of O. felineus through Asian and European territories after severe bottleneck points to a high dispersal potential of this trematode species.